BIOBLEACHING PELEPAH SAWIT SEBAGAI BAHAN BAKU PEMBUATAN NITROSELULOSA MENGGUNAKAN ENZIM XYLANASE - Putri, Medonna Febrina; Sari, Dita Permata; Caesari, Adisty; Miranda, Gilda (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Palm midrib is a waste which produced from palm plantations and contained of 35% cellulose-Î±. Cellulose-Î± can be used as raw material for nitrocellulose if the purity is more than 92%. To improve the purity of cellulose-Î±, palm midrib have to go through some process of purification. Most of purification agent of cellulose-Î± is chemicals using, which it will give a bad impact to environment. Xylanase is a group of enzymes that have the ability to hydrolyze hemicellulose and damage xilose bonds as a constituent of xylan in the hemicellulose. The purpose of this research is to utilize an agent xylanase enzyme purification of cellulose-Î± and produce nitrocellulose from palm midrib. Before purification, palm midrib is extracted to eliminate the extractive substances then hydrolyzed with extract the extract solution ash of palm empty fruit bunches. The condition of purification process is 50 oC,60 oC and 70oC temperature variations, volume 1,2 and 3 ml enzyme, pH at 4,5 and 6 as well as the time for 60,90 and 120 minutes. From this research, the highest purity cellulose-Î± obtained at pH 6, temperature of 60oC, the enzyme 3 ml volume and time for 90 which reached 97.55%.Keywords: Cellulose Alpha, Nitrocellulose, Palm Midrib, Xylanase Enzyme